Dardistan in 1866, 1886 and 1893 - Leitner, G.W., (Brill | Manohar Publishers & Distributors, 2024)
Dardistan, situated between the frontiers of Kashmir and Afghanistan, is mentioned in Greek and Roman texts. Many Greek and Roman writers such as Arrian, Strabo, Alexandrius, and Pliny the Elder have described the region in their respective accounts. The ancient Gandhara was located in this region. However, this region came into much prominence under the British. This work by Leitner is an ethnographical study of the region in the late nineteenth century. The first half of the account covers various legends, customs, and songs composed in the region, which were mostly composed in Shina, a dialect spoken in Kashmir Valley. Folklores containing demons, customs, old fables, manners, etc., are covered. The author touches upon different aspects of human life, birth ceremonies, marriage, funeral, holidays, and also different governments formed in this region. Special emphasis is given to areas like Gilgit, Yasin, Chitral, Nagyr, Hunza, etc. Chronology of the history of Dards, wars against Kashmir, etc., is mentioned. Another important aspect covered is the religions, geography, castes, and races of the Dardistan. The latter half has appendices containing various events in Chilas and Chitrals, languages, anthropological observations, sciences, and secret religions practiced in the region.